Characterization of the NT2‐derived neuronal and astrocytic cell lines as alternative in vitro models for primary human neurons and astrocytes. Issue 9 (7th May 2014) - Haile, Yohannes; Fu, Wen; Shi, Beipei; Westaway, David; Baker, Glen; Jhamandas, Jack; Giuliani, Fabrizio
<x xml:space="preserve">Abstract</x> Primary human fetal neurons and astrocytes (HFNs and HFAs, respectively) provide relevant cell types with which to study in vitro the mechanisms involved in various human neurological diseases, such as multiple sclerosis, Parkinson's disease, and Alzheimer's disease. However, the limited availability of human fetal cells poses a significant problem for the study of these diseases when a human cell model system is required. Thus, generating a readily available alternative cell source with the essential features of human neurons and astrocytes is necessary. The human teratoma‐derived NTera2/D1 (NT2) cell line is a promising tool from which both neuronal and glial cells can be generated. Nevertheless, a direct comparison of NT2 neurons and primary HFNs in terms of their morphology physiological and chemical properties is still missing. This study directly compares NT2‐derived neurons and primary HFNs using immunocytochemistry, confocal calcium imaging, high‐performance liquid chromatography, and high‐content analysis techniques. We investigated the morphological similarities and differences, levels of relevant amino acids, and internal calcium fluctuations in response to certain neurotransmitters/stimuli. We also compared NT2‐derived astrocytes and HFAs. In most of the parameters tested, both neuronal and astrocytic cell types exhibited similarities to primary human fetal neurons and astrocytes. NT2‐derived neurons and astrocytes are reliable in vitro tools and a renewable cell source that can serve as a valid alternative to HFNs/HFAs for mechanistic studies of neurological diseases. © 2014 Wiley Periodicals, Inc.